2016
DOI: 10.1001/jamadermatol.2015.4763
|View full text |Cite
|
Sign up to set email alerts
|

Personal Burden of Isotretinoin Therapy and Willingness to Pay for Electronic Follow-up Visits

Abstract: The requirements that iPLEDGE, a computer-based risk management program (http://www.ipledgeprogram.com), places on prescribing isotretinoin typically mean that patients are seen on a monthly basis in the physician's office for 5 to 6 months, 1 which may lead to time and financial burdens on patients and caregivers, such as missed work and school. To our knowledge, these losses of time have not previously been quantified in the literature. Electronic visits (e-visits) represent a potential alternative to some f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 3 publications
0
33
0
Order By: Relevance
“…Furthermore, two recent articles have highlighted the potential unintended barriers that such stringent compulsory programs can have, and indeed the potential effect of delay to starting treatment or premature stopping treatment in some cases, particularly in certain population groups, due to the inconvenient nature of the programs. 42,43 In 2018, the European Medicines Agency completed its review of retinoid medicines and confirmed that an update of pregnancy prevention measures was needed. 44…”
Section: Side Effects Of Oral Isotretinoinmentioning
confidence: 99%
“…Furthermore, two recent articles have highlighted the potential unintended barriers that such stringent compulsory programs can have, and indeed the potential effect of delay to starting treatment or premature stopping treatment in some cases, particularly in certain population groups, due to the inconvenient nature of the programs. 42,43 In 2018, the European Medicines Agency completed its review of retinoid medicines and confirmed that an update of pregnancy prevention measures was needed. 44…”
Section: Side Effects Of Oral Isotretinoinmentioning
confidence: 99%
“…Seventy-one (male/female: 34/37) adolescent and 397 adult (male/ female: 166/231) patients were recruited in the study. The median age of adolescent patients was 16 (IQR: 3) (ranging from 13 to 18), while adult patients were 26 (20) (ranging from 19 to 83). The comparative results of the data obtained from the questionnaire for adolescent and adult patients are presented in Table S1.…”
Section: Resultsmentioning
confidence: 99%
“…Although insurance coverage remains a barrier to teledermatology use in most states of the United States, patients are reported to be willing to pay a fee outof-pocket, particularly for shorter waiting times. [18][19][20] Factors such as supply-demand balance, expectations of patients and healthcare providers, socioeconomic level of the society, and social state concept will be effective in planning the reimbursement. We think that teledermatology should be low-cost as well as cost-effective especially for developing countries in the middle-income trap like Turkey.…”
Section: Discussionmentioning
confidence: 99%
“…The true cost of a medication to a patient is difficult to calculate given differences in regional pricing, availability, personal burden and opportunity costs in leaving work for (Mori et al, 2016) clinician practice patterns, and widely variable levels of laboratory testing (Shinkai, McMichael, & Linos, 2016). The true cost of a medication to a patient is difficult to calculate given differences in regional pricing, availability, personal burden and opportunity costs in leaving work for (Mori et al, 2016) clinician practice patterns, and widely variable levels of laboratory testing (Shinkai, McMichael, & Linos, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…We caution that the present study ignores many other factors that may preclude consideration of cost on treatment options. The true cost of a medication to a patient is difficult to calculate given differences in regional pricing, availability, personal burden and opportunity costs in leaving work for (Mori et al, 2016) clinician practice patterns, and widely variable levels of laboratory testing (Shinkai, McMichael, & Linos, 2016). Moreover, insurance plans, promotional incentives, and rebates all play a role in patient costs.…”
Section: Discussionmentioning
confidence: 99%